The present-day stress field of New South Wales, Australia. Issue 1 (2nd January 2016) - Rajabi, M.; Tingay, M.; Heidbach, O.
ABSTRACT: The Australian continent displays the most complex pattern of present-day tectonic stress observed in any major continental area. Although plate boundary forces provide a well-established control on the large-scale (>500 km) orientation of maximum horizontal stress (SHmax ), smaller-scale variations, caused by local forces, are poorly understood in Australia. Prior to this study, the World Stress Map database contained 101 SHmax orientation measurements for New South Wales (NSW), Australia, with the bulk of the data coming from shallow engineering tests in the Sydney Basin. In this study we interpret present-day stress indicators analysed from 58.6 km of borehole image logs in 135 coal-seam gas and petroleum wells in different sedimentary basins of NSW, including the Gunnedah, Clarence-Moreton, Sydney, Gloucester, Darling and Bowen–Surat basins. This study provides a refined stress map of NSW, with a total of 340 (A–E quality) SHmax orientations consisting of 186 stress indicators from borehole breakouts, 69 stress measurements from shallow engineering methods, 48 stress indicators from drilling-induced fractures, and 37 stress indicators from earthquake focal mechanism solutions. We define seven stress provinces throughout NSW and determine the mean orientation of the SHmax for each stress province. The results show that the SHmax is variable across the state, but broadly ranges from NE–SW to ESE–WNW. The SHmax is approximately E–W to ESE–WNW in the Darling Basin and Southeastern Seismogenic Zone that covers the west and south of NSW, respectively. However, the present-day SHmax rotates across the northeastern part of NSW, from approximately NE–SW in the South Sydney and Gloucester basins to ENE–WSW in the North Sydney, Clarence-Moreton and Gunnedah basins. Comparisons between the observed SHmax orientations and Australian stress models in the available literature reveal that previous numerical models were unable to satisfactorily predict the state of stress in NSW. Although clear regional present-day stress trends exist in NSW, there are also large perturbations observed locally within most stress provinces that demonstrate the significant control on local intraplate sources of stress. Local SHmax perturbations are interpreted to be due to basement topography, basin geometry, lithological contrasts, igneous intrusions, faults and fractures. Understanding and predicting local stress perturbations has major implications for determining the most productive fractures in petroleum systems, and for modelling the propagation direction and vertical height growth of induced hydraulic fractures in simulation of unconventional reservoirs.